Pengaruh Pengembangan Karir, Motivasi Kerja, Dan Kepuasan Kerja Terhadap Loyalitas Karyawan PT. Magnum Attack Indonesia Kota Malang - Adela, Diva; Arifin, Rois; Slamet, Afi Rachmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze whether there is an influence of career development, work motivation, and job satisfaction on employee loyalty of PT Magnum Attack Indonesia, with a focus on the production employees of PT Magnum Attack Indonesia. The method used is quantitative with a survey approach, distributing questionnaires to 87 respondents. Data analysis was conducted using multiple linear regression with SPSS 27 to identify the effect of independent variables on employee loyalty. The findings of this study are career development has a significant effect on employee loyalty, work motivation has a significant effect on employee loyalty and job satisfaction has a significant effect on employee loyalty. Keywords: Career Development, Work Motivation, Job Satisfaction, Employee Loyalty